The toxic influence of paraquat on hippocampal neurogenesis in adult mice. (August 2017) - Li, Kaikai; Cheng, Xinran; Jiang, Jinhua; Wang, Jiutao; Xie, Jiongfang; Hu, Xinde; Huang, Yingxue; Song, Lingzhen; Liu, Mengmeng; Cai, Leiming; Chen, Liezhong; Zhao, Shanting
Abstract: Paraquat, a fast-acting non-selective contact herbicide, is considered an etiological factor related to Parkinson's disease. This study investigated its effects on hippocampal neurogenesis and cognition in adult mice as well as possible mechanisms for the effects. We administered paraquat (1.25 mg/kg, intraperitoneal injection, i.p.) and an equal volume of normal saline for 3 weeks to adult male C57BL/6J mice. The results showed that hippocampus-dependent spatial learning and memory was significantly impaired in paraquat-treated mice. Moreover, paraquat administration inhibited the proliferation of neural progenitor cells, and impaired the survival and altered the fate decision of newly generated cells in the hippocampus. The expression levels of caspase-3 and glial fibrillary acidic protein were significantly higher in paraquat-treated mice than in control mice. Interestingly, paraquat reduced the phosphorylation of Akt, but did not affect the total amount of Akt. In conclusion, our findings suggest that paraquat negatively affected adult hippocampal neurogenesis and cognition function. Highlights: Paraquat inhibited cell proliferation and induced cell death in vitro . Paraquat exposure impaired spatial memory in adult mice. Paraquat treatment with paraquat impaired the survival and altered the fate decision. Paraquat reduced the phosphorylation of Akt.